REGULARITIES OF FORMATION OF STRUCTURAL AND MECHANICAL PROPERTIES OF THE NONSTICK COVERINGS MODIFIED BY NANOSTRUCTURED MATERIALS - D. M. Kukij; Yu. A. Nikolaychik; R. S. Filimonenko (Литьë и металлургия, 2013)
The regularities of formation of the nonstick covering properties on the basis of high-refractory aluminosilicate filler at modifying of coating with nanostructured materials (AlOOH) were studied.